Report of the IOI Workshop “Creating an International Informatics Curriculum for Primary and High School Education” - Ackovska, Nevena; ERDŐSNÉ NÉMETH, Ágnes; Stankov, Emil; Jovanov, Mile (Vilnius University Press, 2015)
This report entangles the endeavors undertaken during the IOI Workshop “Creating an International Informatics Curriculum for Primary and High School Education”. Considering the need to discuss the role of informatics in the primary and secondary education, the Workshop participants tried to encapsulate several activities that might give insight on how to treat this issue with success. An overview of the current situation with the informatics education in thirteen countries was presented. Further, a group work took place considering relevant topics in creating informatics curricula and computational thinking. A fruitful discussion that considered establishing guidelines and further steps in creating informatics curricula and some ways to promote informatics concluded the Workshop.